Clinical evaluation of removable partial denture treatment in the Lubuk Minturun, Padang City - Arief Waskitho; Dina Auliya Amly; Fahmi Yunisa; Hastoro Pintadi; Bellinda Aprillia Mirnacantika (Community Empowerment, 2023)
Dental and oral health problems are one of the health problems that require special attention in Indonesia. The most common dental health problem in Indonesia is cavities or dental caries. The incidence of caries in Indonesia is very high, reaching 88.8% of the total population of Indonesia. This high number is influenced by several factors, one of which is daily intake of high-sugar foods, bad habits of the community that can affect dental and oral health, and low public awareness of dental and oral health. Low public awareness of oral health has led to low public interest in caring for their teeth. This causes the teeth to no longer be treated, resulting in tooth loss. Tooth loss can affect a person's speech, mastication, and aesthetic functions. Based on the conditions experienced by the Indonesian people, rehabilitative measures are needed, namely in the form of denture treatment in cases of tooth loss. The purpose of this community service is to provide services to the people of Indonesia through the act of making free dentures which are expected to overcome complaints of tooth loss experienced by the surrounding community and an evaluation of the treatment of the programs that have been implemented. The community service method is to carry out rehabilitative activities by making removable partial dentures free of charge. The results of the community service by dentures treatments could improve dental and oral health of the subjects seen 100% satisfaction of post-treatment evaluations.